Perspective sample of root chicory - O. M. Vyutnova; T. Yu. Polyanina; I. A. Novikova (Овощи России, 2019)
Relevance. One of the types of agricultural raw materials for the food industry is the root chicory, the product from the roots of which is produced in pure form, as well as is an important component in the production of tea and coffee drinks, confectionery. Its value is determined by the content in the roots of inulin, fructose, intibin and chicory. Despite the great economic importance and economic profitability of chicory cultivation, in recent years, the local processing industry is not provided with this type of raw material and is forced to buy the product from dried root crops in other countries, such as Ukraine, Italy and India. Modern agricultural production is in dire need of new varieties of root chicory, combining high yields and chemical and technological qualities, having the form of a root crop suitable for mechanized harvesting, and adapted to cultivation in soil and climatic conditions of the Non-chernozem zone. Purpose of work: to assess the nature of the impact of ultraviolet radiation in the time mode on watermelon seeds using cytogenetic analysis.Material and methods. The article describes the results of the test in the control nursery of a new sample of chicory root with 0428 selection of Rostov OSC.Results. As a result of breeding work, a promising sample of root chicory. It was isolated early maturing, with high yields and economically valuable properties, root crop truncated, suitable for mechanized harvesting by commercially available machines.